2020
DOI: 10.1109/access.2020.2981689
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Machine Learning Techniques for Chronic Kidney Disease Prophecy

Abstract: Chronic Kidney Disease (CKD) implies that the human kidneys are harmed and unable to blood filter in the manner which they should. The disease is designated ''chronic'' in light of the fact that harm to human kidneys happen gradually over a significant time. This harm can make wastes to build up in your body. Many techniques and models have been developed to diagnos the CKD in early-stage. Among all techniques, Machine Learning (ML) techniques play a significant role in the early forecasting of different kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…In Table 6, we compare the proposed method with other recent CKD prediction research works, including an optimized XGBoost method [38], a probabilistic neural network (PNN) [39], and a method using adaptive boosting (AdaBoost) [40]. The other research works include a hybrid classifier of NB and decision tree (NBTree) [41], XGBoost [42], and a 7-7-1 MLP neural network [43]. Table 6.…”
Section: Methods Accuracy (%)mentioning
confidence: 99%
“…In Table 6, we compare the proposed method with other recent CKD prediction research works, including an optimized XGBoost method [38], a probabilistic neural network (PNN) [39], and a method using adaptive boosting (AdaBoost) [40]. The other research works include a hybrid classifier of NB and decision tree (NBTree) [41], XGBoost [42], and a 7-7-1 MLP neural network [43]. Table 6.…”
Section: Methods Accuracy (%)mentioning
confidence: 99%
“…A number of studies have shown that feature selection improves the generalization capabilities of the classification models [6][7][8][9][10][11][12]. Feature selection is similar to dimensionality reduction whereas the objective of the former is to retain the semantics present in the original dataset while the latter transforms the data in such a manner as the overall dimensions of the data are reduced [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the domain of medical data mining, several intelligent clinical decision support systems are designed which tend to automate the diagnosis process [6,42]. These decision systems employ machine learning techniques that assist physicians in the diagnosis and treatment of CKD in an efficient manner [6,7,8]. Based on a number of important indicators such as blood pressure, albumin levels, blood and urea tests, potassium, and other comorbidities e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations